20 Lessons learned from the NNEdPro Nutrition and COVID-19 taskforce. (12th April 2022) - Crocombe, Dominic; Mcauliffe, Shane; Kohlmeier, Martin; Ray, Sumantra
Abstract : Acknowledgements: : NNEdPro Nutrition and COVID-19 Taskforce (Named authors plus James Bradfield, Luke Buckner, Harrison Carter, Elaine Macaninch, Suzana Almoosawi, Timothy Eden, Emily Fallon, Claudia Mitrofan, Niky Raja, Sucheta Mitra, Matheus Abrantes, Lynn Haynes) and BMJ Nutrition, Prevention and Health. Background: Nutritional issues relating to the COVID-19 pandemic span clinical nutrition in acute patients to impacts on global dietary patterns and food security. In March 2020, the NNEdPro Global Centre for Nutrition and Health established a rapid-response Nutrition and COVID-19 Taskforce to help the organisation navigate the initial phases of the pandemic and make a constructive contribution to the scientific landscape. 1–3 Objectives: To highlight lessons learned over 6 months (March-September 2020) of the COVID-19 pandemic in understanding the role(s) of nutrition. Methods: Critical and constructive reflections from Taskforce co-chairs and lead scientific members based on a 6-month summative webinar and journal club examining the strength of evidence and key gaps. Results: Successes in Taskforce operations include pooling a broad range of expertise including clinical medicine, nutrition and dietetics, research, public health, and communications. Pre-existing NNEdPro operations were predominantly online and dedicated virtual meetings supported the proactive collation of key resources relating to nutrition and COVID-19 with production of public-facing information summaries. Academic collaboration with partner organisations, including BMJ Nutrition, Prevention & Health, has focused research priorities and produced contributions to the scientific landscape. 4 Challenges included managing the sense of urgency, particularly earlier in the pandemic and driven by an unease of the unknown, both at organisational level and in the need to translate nutrition knowledge to COVID-19 sensitive practice. A collaborative, scientific and politically neutral approach was intended to ensure the quality of outputs and the avoidance of hasty conclusions. Other challenges have been maintaining relevance to all geographic regions given the global variation of COVID-19 and maximising the reach of outputs to stakeholders who would benefit most from them. More recently the Taskforce has provided key inputs to consensus in a national guideline agency and global advisory bodies. Further progress will require involvement of researchers and innovators, policymakers, practitioners, patients and the public. Discussion/Conclusion: This Taskforce has already made a significant contribution to the scientific conversation about food and nutrition in the prevention and management of COVID-19. Future work should focus on multiple-stakeholder collaboration to transform research into positive action at all levels (from patient to policy) for the benefit of public health. References: NNEdPro Global Centre for Nutrition and Health. COVID19: Useful resources. nnedpro.org.uk. [Online] [Cited: September 7, 2020.] https://www.nnedpro.org.uk/coronavirus. NNEdPro Global Centre for Nutrition and Health. COVID19: Nutrition Resources. nnedpro.org.uk. [Online] [Cited: September 7, 2020.] https://www.nnedpro.org.uk/covid-19nutrition-resources. NNEdPro Global Centre for Nutrition and Health. Combatting COVID-19: A 10-point summary on diet, nutrition and the role of micronutrients. nnedpro.org.uk. [Online] [Cited: September 7, 2020.] https://www.nnedpro.org.uk/post/combatting-covid-19. Dietary micronutrients in the wake of COVID-19: an appraisal of evidence with a focus on high-risk groups and preventative healthcare. McAuliffe, Shane, et al. s.l. : BMJ Nutrition, Prevention & Health, 2020, Vols. bmjnph-2020-000100. doi: 10.1136/bmjnph-2020-000100.